Review of clinical studies comparing meningococcal serogroup C immune responses induced by MenACWY-TT and monovalent serogroup C vaccines. Issue 7 (3rd July 2021) - Serra, Lidia; Knuf, Markus; Martinón-Torres, Federico; Yi, Kevin; Findlow, Jamie
ABSTRACT: Many countries are replacing meningococcal serogroup C (MenC) conjugate vaccines (MCCV) with quadrivalent conjugate (MenACWY) vaccines, such as MenACWY-TT (Nimenrix®). This review examined eight studies comparing MenC immune responses induced by MenACWY-TT and MCCV to determine if these data support these changes. MenC serum bactericidal antibody levels using human (hSBA) or rabbit complement (rSBA) were evaluated at 1 month postvaccination. Overall, ≥98.4% of infants administered 2 + 1 MenACWY-TT or MCCV schedules had rSBA titers ≥1:8 postprimary and postbooster vaccination; hSBA titers ≥1:8 were similar. In toddlers administered single MenACWY-TT or MCCV doses, ≥97.3% had rSBA titers ≥1:8 postvaccination; percentages with hSBA titers ≥1:8 were higher post-MenACWY-TT. Of children and adolescents receiving primary and booster MenACWY-TT and MCCV, ≥98.6% had rSBA titers ≥1:8; all children receiving MenACWY-TT or MCCV booster had hSBA titers ≥1:8 postdosing. MenC immune responses induced by MenACWY-TT are robust and generally comparable/superior to MCCV, supporting changes to recommendations.